Scientific Awareness in Homeopathic Practitioners and Their Scientific Responsibility to Develop as "Healing Scientists". - Rutten, Lex (American Journal of Homeopathic Medicine)
Homeopathy is regarded as unscientific by many, but this is caused by a restrictive definition of science. If we include Bayesian statistics in the scientific repertoire, an experience driven method like homeopathy acquires a solid scientific rectification, and that can be translated into prognostic factor research. The experience that underlies the scientific development of homeopathy can only come from its practitioners. Therefore, practitioners should become aware of possible bias in their observations and they should understand basic Bayesian statistics. The increasing application of statistical algorithms in repertorization software also necessitates that homeopathic practitioners be aware of the advantages and disadvantages of statistics.